HUBUNGAN PENGUASAAN KOSAKATA BIDANG LINGKUNGAN DENGAN KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 8 PADANG - Anizah, Anizah; Basri, Irfani; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This article is written to find out the correlation between vocabulary mastery in environtment sector with the ability of writing the explanation text by eighth grade students of SMP Negeri 8 Padang. The type of this research is quantitative research. The method used in this research is descriptive method which uses correlational research design. The populations of this research are eighth grade students of SMP Negeri 8 Padang which consist of 193 students who are divided into seven classes. The samples of this research are 42 students. This research consists of two variables, which are independent variable (vocabulary mastery in environtment sector of eighth grade students of SMP Negeri 8 Padang) and dependent variable (the ability of writing explanation text by eighth grade students of SMP Negeri 8 Padang). The research’s results show that for the ability of writing explanation text is needed the vocabulary mastery in environtment sector. From the result of the research, it can be concluded that there is significant relation (meaningful) between the vocabulary mastery in environtment sector with the ability of writing explanatiom text by eighth grade students of SMP Negeri 8 Padang on degree of freedom n-1 at significant degree 95% which the tcount is bigger that ttable, which is 9,8 > 1,683. Kata kunci: penguasaan kosakata bidang lingkungan, menulis teks eksplanasi